Analysis of planning for the audit of the cooperative's financial statements at the Cooperatives Assisted by the Department of Cooperatives and MSMEs in Bandung City - Luthvianty, Yopie; Sefira, Reva Dwina; Hasyim, Muhammad Ardi Nupi (Keynesia : International Journal of Economy and Business, 2022)
This study aims to determine whether the procedures and planning for the audit of the financial statements of the cooperatives under the supervision of the Public Accounting Firm are by the Auditing Standards. This research method uses a descriptive qualitative method by analyzing the cooperative financial statement data that has been audited by the Bandung City Cooperative Service based on interviews and other field findings. Primary data obtained directly from the results of interviews with the staff of supervision and auditing, and secondary data in question can be in the form of audit planning documentation of financial statements, which are summarized in the Audit Work Paper and general guidelines for auditing financial statements (Audit Manual) of the Bandung City Cooperative Office. This research at the Department of Cooperatives, Micro, Small, and Medium Enterprises in Bandung City is located on Jl. Kawaluyaan No. 2 Jatisari, Buahbatu District, Bandung City. After conducting an analysis based on interviews and documentation, the Bandung City Cooperative Service does not yet have an audit plan used as a guide in carrying out supervision and examination of the financial statements of Cooperatives in the City of Bandung. The inspection or audit should be carried out by a Public Accounting Firm and a public accountant because the task of the Bandung City Cooperative Service is only to collect cooperative data that will be examined. So after analyzing the financial statement audit planning according to SPAP, it can be seen that the design of the Bandung City Cooperative financial statement audit planning is not by the financial statement audit planning according to SPAP.